Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics